2011
DOI: 10.1016/j.crme.2010.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Laminar free convection in undulated cavity with non-uniform boundary conditions

Abstract: In the present work, the influence of non-uniform boundary conditions on natural convection in inclined rectangular cavities differentially heated is studied. The hot wall is wavy with three undulations. The aspect ratio of the cavities has also been changed. Various inclination angles were performed. The flow and the heat transfer are calculated by solving both Navier-Stokes and the energy equations with finite volume method in the primitive formulation. The sinusoidal distribution of temperature is imposed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Oztop et al (2011) considered the impact of volumetric heat sources on flow structures inside a wavy-walled cavity. Sabeur-Bendehina et al (2011) studied the convection flow with non-uniform boundary conditions in an inclined wavy cavity. Dogonchi et al (2019b) investigated the nanofluid flow in parallel disks under the effects of several physical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Oztop et al (2011) considered the impact of volumetric heat sources on flow structures inside a wavy-walled cavity. Sabeur-Bendehina et al (2011) studied the convection flow with non-uniform boundary conditions in an inclined wavy cavity. Dogonchi et al (2019b) investigated the nanofluid flow in parallel disks under the effects of several physical parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, knowledge about flow and heat transfer through wavy surfaces becomes important in this context. Solar collectors, condensers in refrigerators, cavity wall insulating systems, grain storage containers, industrial heat radiators, for example, are a few of many applications where wavy surfaces are encountered to transfer small or large scale heat [1,2]. The focus on the area of flow and heat transfer past wavy surfaces in complex enclosures like square, trapezoidal, and rectangular has been intensifying over the years due to the increasing interest of researchers from applied mathematics, mechanical, and chemical engineering as well as from biomechanics and engineering mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Saha et al [9] solved the natural convection problem for sinusoidal and inclined corrugation geometry and different heat source sizes. Recently, Bendehina et al [10] reported a series of numerical simulations on laminar natural convection in inclined rectangular cavities with undulations and a sinusoidal temperature distribution on the cold wall. A thorough analysis conducted by Chin-Lung Chen et al [11] highlighted the effects of various shaped concave enclosures on convection heat transfer.…”
Section: Introductionmentioning
confidence: 99%